Management Ergonomics Sector Analysis Oil Palm Plantation - Agrasan Duha (Syntax Corporation Indonesia, 2024)
Indonesia, the world’s largest palm oil producer, significantly impacts global crude palm oil (CPO) production. Despite its economic value, manual labor in oil palm plantations often involves non-ergonomic practices, particularly in tasks like loading and unloading, leading to worker fatigue and increased risks of Musculoskeletal Disorders (MSDs). This research aims to evaluate ergonomic risks and MSD prevalence among oil palm workers by analyzing body posture during daily tasks. Data were collected using the RULA method, Nordic Body Map, and environmental measurements, supported by interviews and observations. Findings reveal that improper lifting and posture during harvesting contribute to fatigue and MSDs among workers. Recommendations for improvement include regular ergonomic training, adjustments to work posture, and the addition of safety equipment like fire extinguishers. By implementing these changes, the study seeks to improve worker safety, minimize MSD occurrences, and boost productivity in oil palm plantations. These insights are vital for ensuring sustainable practices in the industry and promoting the well-being of plantation workers.